Kantian Right and Poverty Relief - Andrea Faggion (Ethic@: an International Journal for Moral Philosophy)
I have two goals in this paper. First, I want to determine whether Kant’s justification for state programs for poverty relief in The Doctrine of Right is based on 1) Kantian duties of virtue,  2) Kantian duties of right, or instead merely on 3) instrumental arguments regarding the preservation of a State as such.  I claim that the last alternative is the correct one. Second, I will argue, against Kant himself, that even his merely instrumental arguments for public programs for poverty relief are ruled out by his doctrine of right. My conclusion is that, perhaps surprisingly, the only genuinely Kantian way to provide poverty relief is privately, just as Libertarians have argued.